Strategic Public Relations as a Driver of Institutional Positioning and Competitive Advantage in Higher Education - Siti Aminah; Agus Maimun; Indah Aminatuz Zuhriyah (Business and Applied Management Journal, 2025)
This study aims to analyze the role of strategic public relations management in enhancing institutional positioning and competitive advantage in higher education. Employing a qualitative approach with a multi-case study design, data were collected through in-depth interviews, observation, and documentation involving institutional leaders, public relations practitioners, academics, students, and alumni. The findings indicate that strategic public relations serves as a foundational mechanism for institutional positioning through public needs analysis, identity strengthening, and integrated communication strategies. Furthermore, integrated communication encompassing media relations, digital branding, academic publications, and stakeholder engagement plays a critical role in shaping institutional image and reputation through message consistency. Strategic public relations also contributes significantly to competitive advantage by fostering public trust, increasing institutional visibility, and strengthening differentiation. The study implies that strategic public relations functions as a dynamic capability that links internal institutional quality with external public perception, transforming communication into strategic value. These findings offer theoretical contributions by integrating public relations, positioning, reputation, and competitive advantage into a unified framework, while practically providing guidance for higher education institutions in designing effective strategic communication to enhance competitiveness in a dynamic environment.